Autonomic responses induced by aerobic submaximal exercise in obese and overweight adolescents - Santana, Milana D. R.; Kliszczewicz, Brian; Vanderlei, Franciele M. [UNESP]; Monteiro, Larissa R. L.; Martiniano, Eli Carlos; De Moraes, Yasmim M.; Mangueira, Luana B.; Alcantara, Guilherme C.; Da Silva, José Ramon A.; Benjamim, Cicero Jonas R.; Oliveira, Fernando R. [UNESP]; Valenti, Vitor E. [UNESP] (Cambridge University Press (CUP), 2019)
Background: Graded exercises tests are performed in adult populations; nonetheless, the use of this type of assessment is greatly understudied in overweight and obese adolescents. Objective: To investigate heart rate autonomic responses to submaximal aerobic exercise in obese and overweight adolescents. Methods: We recruited 40 adolescents divided into two groups: (1) overweight group comprising 10 boys and 10 girls between Z-score +1 and +2 and (2) obese group comprising 10 boys and 10 girls above Z-score >+2. Heart rate variability was analysed before (T1) and after exercise (T2-T4) on treadmill at a slope of 0%, with 70% of the maximal estimated heart rate (220 - age) for 20 minutes. Results: Heart rate in the overweight group was: 93.2±10.52 bpm versus 120.8±13.49 bpm versus 94.6±11.65 bpm versus 93.0±9.23 bpm, and in the obese group was: 92.0±15.41 bpm versus 117.6±16.31 bpm versus 92.1±12.9 bpm versus 91.8±14.33 bpm. High frequency in the overweight group was: 640±633.1 ms 2 versus 84±174.66 ms 2 versus 603.5±655.31 ms 2 versus 762.6±807.21 ms 2 , and in the obese group was: 628.4±779.81 ms 2 versus 65.4±119.34 ms 2 versus 506.2±482.70 ms 2 versus 677.9±939.05 ms 2 ; and root mean square of successive differences in the overweight group was: 37.9±18.81 ms versus 10.9±8.41 ms versus 32.8±24.07 ms versus 36.7±21.86 ms, and in the obese group was: 38.7±23.17 ms versus 11.5±8.62 ms versus 32.3±16.74 ms versus 37.3±24.21 ms. These values significantly changed during exercise compared with resting values in overweight and obese groups. Moreover, we also reported no significant difference of resting parasympathetic control of heart rate between obese and overweight adolescents. Conclusion: There was no significant difference of autonomic responses elicited by submaximal aerobic exercise between overweight and obese adolescents.
Keywords: Adolescent; adolescent health; autonomic nervous system; cardiovascular system; obesity